2018
DOI: 10.1021/acssuschemeng.7b03303
|View full text |Cite
|
Sign up to set email alerts
|

Facilities Location for Residual Biomass Production System Using Geographic Information System under Uncertainty

Abstract: Biomass is a renewable resource that has attractive characteristics for manufacturing many types of products such as biofuels, specialty chemicals, and energy generation. Several studies have addressed diverse important features such as new technologies for biomass treatment, approaches for potential location of refineries, models to evaluate existing relationships between availability and price, among others. However, two important issues need to be considered: potential locations for biomass processing syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…(2018) [54] did in their study. One example of including emission estimation was supplied by Furubayashi and Nakata (2018) [53], who used mathematical expressions for energy consumption.…”
Section: Combinations Of Methods In Generalmentioning
confidence: 88%
“…(2018) [54] did in their study. One example of including emission estimation was supplied by Furubayashi and Nakata (2018) [53], who used mathematical expressions for energy consumption.…”
Section: Combinations Of Methods In Generalmentioning
confidence: 88%
“…A GIS-based model taking into account various features connected to a geographic region in order to determine the location of biomass-processing facilities considering also uncertainty factors [35]. These factors are connected to the availability of crop residues, other environmental, financial, weather, or even social constraints.…”
Section: Strategic Planningmentioning
confidence: 99%
“…Davis et al [6] and Baustert and Benetto [14] suggest that ABM could be used to generate foreground data, also known as inventory, which could then be coupled with LCA. In addition to ABM, geographical information systems (GIS) are often used to analyse spatial information, which is important for collecting inventories in local contexts [15]. A review by Aalto et al [13] suggests that there are multiple benefits of coupling GIS and ABM with LCA; however, their study found no research that combines all three modelling approaches.…”
Section: Introductionmentioning
confidence: 99%